Simulated Mass, Heat and Freshwater Budgets of the Artic Mediterranean - Present and Future - Bethke, Ingo (The University of Bergen, 2004)
The majority of recent climate forecast studies suggest a dramatic thinning of the Arctic multi year ice and eventually the disappearing of all summer ice within just a few decades. Moreover, in the maritime Arctic a large number of regional impacts are re ected in changes of the ocean circulation, energy balance, and hydrological cycle. The Bergen Climate Model is one of the approximately 20 AOGCMs which simulate possible near-future climates while trying to distinguish between human caused changes and natural variability. To address the question of how the ocean contributes to the predicted or probably already observed Arctic climate change is subject of this work. With the help of budget and ux products of mass, heat and freshwater, an attempt is made to propose quantitatively consistent answers to these problems.